Leaf area development and yield of cassava in response to pruning of shoots and the late supply of nitrogen and potassium - Mota, Lydia Helena S.O. [UNESP]; Fernandes, Adalton M. [UNESP]; Assunção, Natália S. [UNESP]; Leite, Hugo M.F. [UNESP] (Wiley, 2020)
This study evaluated leaf area development, leaf nutritional content, and yield of pruned/unpruned cassava supplied with nitrogen (N) and potassium (K) during its second vegetative cycle. Two field experiments were conducted in a randomized complete-block design with split-plots and four replications. The treatments consisted of four management approaches that combined pruning/not pruning with or without K as the main plot and four N application rates (0, 50, 100, and 200 kg ha−1 N) as the subplots. The results revealed that an evaluation of the nutritional status of cassava during its second vegetative cycle should be considered if shoot pruning has been conducted because pruned plants had higher concentrations of N, P, and K in their leaves, and unpruned plants exhibited leaves with higher Ca, Fe, and Mn concentrations. Pruning of cassava shoots during the autumn/winter resting phase did not negatively affect root yield and may represent a recommended management practice for cassava cultivation. In soils with a medium level of K availability, K provision during the second cassava growth cycle is unnecessary because the application of K did not increase leaf reconstitution or yield components in either pruned or unpruned plants. The late application of N improved the nutritional status of cassava plants and increased their leaf area during the second growth cycle. Cassava root, starch, and flour yields increased in a linear fashion in response to the late application of N.